Reading Overload: A Multiples Case Study of Public and Private Primary Schools in Akure, Nigeria - Adepoju, Adetokunboh Abayomi (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2025)
The study examined the extent of excessive reading materials used in selected public and private primary schools in Akure, the capital of Ondo State, Nigeria with a view to determining overloading ESL learners with reading materials and how this affects their learning experiences. The study adopted Cognitive Load Theory and investigated the number of reading materials officially recommended in the curriculum, the actual number used in public and private primary schools, and the influence of material quantity on pupils’ comprehension. A multiple case study design was employed, involving eight headteachers, 113 class teachers, four parents, and eight pupils from selected public and private schools. To collect quantitative data, the study used a validated fifteen-item Likert questionnaire. For the qualitative data, in depth interviews and documents were employed. The results rejected the null hypothesis which said ‘There is no significant difference between the quantity of English textbooks used in public and private primary school’ with t-test results t (98) = 2.152, p<0.05, ŋ2 = 0.045. It means although the recommended textbooks were generally considered adequate, private schools frequently prescribed additional materials beyond government requirements. The thematic analysis of qualitative data showed substantial duplications of contents across textbooks, overloading of children and violation of curriculum policy. Based on the findings, it recommends policy enforcement, culturally relevant textbook selection, and reduced redundancy in instructional materials to promote more effective and developmentally appropriate reading practices.